2000
DOI: 10.1177/01461672002611003
|View full text |Cite
|
Sign up to set email alerts
|

Do Messages about Health Risks Threaten the Self? Increasing the Acceptance of Threatening Health Messages Via Self-Affirmation

Abstract: Two stud ies dem on strate that self-image main te nance pro cesses affect the accep tance of per son ally rel e vant health mes sages. Participants who com pleted a self-affir ma tion were less defen sive and more accept ing of health infor ma tion. In Study 1, female par tic i pants (high vs. low rel e vance) read an arti cle link ing caffeine con sump tion to breast can cer. High-rel e vance women rejected the infor ma tion more than did low-rel e vance women; how ever, affirmed high-rel e vance women accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
679
5
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 558 publications
(745 citation statements)
references
References 36 publications
(62 reference statements)
37
679
5
5
Order By: Relevance
“…This study found that self-affirmed participants who were frequent caffeine consumers rated the health-risk information as more convincing and reported greater perceptions of behavioural control in relation to decreasing caffeine consumption, compared to their non-affirmed counterparts. Similarly, Sherman, Nelson & Steele (2000) found that self-affirmed, frequent caffeine consumers reported greater acceptance and less criticism of a message detailing a link between caffeine consumption and breast cancer risk, together with more positive intentions to reduce their caffeine consumption, compared to their non-affirmed counterparts. Furthermore, Klein, Harris, Ferrer & Zajac (2011, study 2) demonstrated that after exposure to message outlining a link between caffeine consumption and breast cancer risk, selfaffirmed frequent caffeine consumers reported increased levels of vulnerability to breast cancer and more positive intentions to reduce their caffeine intake, compared to their non-affirmed counterparts.…”
Section: The Capacity Of Self-affirmation To Promote Positive Changesmentioning
confidence: 90%
See 4 more Smart Citations
“…This study found that self-affirmed participants who were frequent caffeine consumers rated the health-risk information as more convincing and reported greater perceptions of behavioural control in relation to decreasing caffeine consumption, compared to their non-affirmed counterparts. Similarly, Sherman, Nelson & Steele (2000) found that self-affirmed, frequent caffeine consumers reported greater acceptance and less criticism of a message detailing a link between caffeine consumption and breast cancer risk, together with more positive intentions to reduce their caffeine consumption, compared to their non-affirmed counterparts. Furthermore, Klein, Harris, Ferrer & Zajac (2011, study 2) demonstrated that after exposure to message outlining a link between caffeine consumption and breast cancer risk, selfaffirmed frequent caffeine consumers reported increased levels of vulnerability to breast cancer and more positive intentions to reduce their caffeine intake, compared to their non-affirmed counterparts.…”
Section: The Capacity Of Self-affirmation To Promote Positive Changesmentioning
confidence: 90%
“…Such defensive responses can potentially limit the efficacy of health promotion campaigns. Indeed, research has frequently reported that individuals who are at greatest risk of engaging in health-detrimental behaviours, i.e., those whom the health promotion campaigns are targeting, are the ones who are most likely to respond defensively to personally relevant health-risk information (Block & Williams, 2006;Good & Abraham, 2007;Keller, 1999;Sherman, Nelson & Steele, 2000;van Riet & Ruiter, 2011).…”
Section: Application Of Sat To Personally Relevant Health-risk Informmentioning
confidence: 99%
See 3 more Smart Citations